2016
DOI: 10.1016/j.jaci.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Timely follow-up of a GATA2 deficiency patient allows successful treatment

Abstract: Jacobino has received research support from the University of Utrecht (European Research Council stimulation grant). M. Nederend has received research support from the Dutch Technology Foundation (Stichting voor de Technische Wetenshappen project 13017). M. L. Houben has received research support from European Society for Pediatric Infectious Diseases and Dutch Asthma Foundation. R. J. J. van Neerven is employed by FrieslandCampina (Amersfoort, The Netherlands), which was not in any way involved in this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Moreover, there are limited data in this regard. 10, 13 However, three factors play important roles in the indication and timing of transplant: frequency and severity of infections, secondary organ damage such as pulmonary changes, and myeloid progression of cytopenias and cytogenetic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are limited data in this regard. 10, 13 However, three factors play important roles in the indication and timing of transplant: frequency and severity of infections, secondary organ damage such as pulmonary changes, and myeloid progression of cytopenias and cytogenetic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Ciucilli et al reported a young patient who received a transplant from his matched brother using an ablative regimen 75 . Ramazan et al reported a very young patient with Emberger syndrome and MDS who underwent successful myeloablative HSCT with resolution of MDS 76 .…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Thirty patients were previously reported. 11 , 18-20 Data from 500 sporadic adult AML samples (2018-2022) were extracted from the AML database of Toulouse University Hospital registered at the Commission Nationale de l’Informatique et des Libertés (CNIL, #1778920), and sequenced with the same panel, coverage and sensibility of the technique.…”
Section: Methodsmentioning
confidence: 99%